The use of X-ray computed tomography in bio-composite research - Couceiro, José; Sandberg, Dick (Luleå tekniska universitet, Träteknologi, 2016)
X-ray computed tomography (CT), which was introduced in the medical field in the early 1970s, is also a powerful tool for the non-destructive measurement of dynamic processes in wood. For more than 20 years, medical CT has been used in wood research at Luleå University of Technology. The uniqueness of the CT equipment allowsprocesses such as drying, modification; water absorption; internal and external cracking; and material deformation to be studied in temperature- and humidity-controlled environments. The data recorded by the CT scanner during the process is converted into two or three dimensional images that, for instance, can show dynamic moisture behaviour in wood drying and crack formation. This paper provides an overview of the possibilities of using CT in bio-composite research, and shows examples of applications and results that can be particularly difficult to achieve using other methods. A specific focus is on studies on wood products that use combinations with materials such as metal and especially about how to deal with the difficulties that this entails.The practical application of the result is that CT scanning, combined with image processing, can be used for non-destructive and non-contact three-dimensional s tudies of exterior construction elements during water sorption and desorption, to study parameters such as swelling and shrinking behaviour; delamination phenomena; and crack development.